Ways of making online teaching more successful: An autoethnographic study - Bao, Dat (Teaching English as a Foreign Language Journal, 2023)
This article is the author’s professional reflectivity as a TESOL lecturer at an Australian University over the past sixteen years. Observing and responding to students’ interests, concerns, and challenges has allowed this work to take shape. It signifies a range of issues that shape student learning with a strong focus on problematic features of online education practices. These issues include the absence of non-verbal cues, responsive latency, the pressure of teacher multiple-roles, and digital learning boredom. Thanks to collected data from student feedback, conversation with colleagues, and field notes, the author has put together a set of principles and strategies for making teaching and learning in the virtual space a more rewarding experience for both teachers and students. The strategies inclkude making learning content interesting and useful, personalised communication, clear participation protocols, mediation of student workload and participation, scaffolding online learning, organising choices, diversifying approaches to tasks, encouraging student voices, and collaboration with non-teaching staff.